Как находить неисправности в приемнике - Крашенинников Сергей Сергеевич (Издательство ДОСААФ, 1961)
Экземпляры: КХ (20200728) / Инвентарный номер: 0121224 / Сис.шифр: 621396 / Авт.знак: К 78 / ГРНТИ: 47 / ББК: 32